The professional competencies of teachers of hearing-impaired children (Journal of the College of Basic Education, 2022)
The professional competence of teachers of students with special needs is one of the very important things that they should have, without which they cannot carry out their tasks with this type of students as required, especially teachers of students with hearing disabilities, so who is the teacher with high competence? Is she that teacher who knows the causes that lead to cases of hearing impairment, methods of diagnosis, ways of preventing them, avoiding the psychological and social effects arising from the deprivation suffered by those individuals with hearing disabilities, and the methods and means through which they can compensate for what they have lost from the sense of hearing.